The Correlation of Caffeine and Fizzy Drink Consumption and Bone Mineral Density in Women Fertilizer Age in Pekanbaru City - Rini Hariani Ratih; Yusmaharani Yusmaharani; Nurmaliza Nurmaliza (STIKes Patria Husada Blitar, 2022)
Osteoporosis is defined as a decrease in bone mass and is characterized by an increased risk of fracture due to bone fragility. Prevention of low bone density can be done by optimizing the formation of bone mass at the time of growth, namely the age of 20-35 years. Research on osteoporosis in Jakarta in 2011 on subjects aged 20-25 years, stated that 6.3% had osteoporosis and 51.1% had osteopenia (pre-osteoporosis). The aim of the study was to identify the correlation of caffeine and soft drinks consumption toward bone mineral density status in women of childbearing age. This study was a quantitative analytic study, with a cross sectional research design. The sample was women of childbearing age who were in the work area of Tampan District as many as 399 people. The Chi-Square test showed the effect of caffeine consumption and soft drinks on the status of bone mineral density in women of childbearing age with a P value of 0.000 < Alpha 0.05 with a large OR of 24,330 (95% CI: 10,174- 58.182), meaning that respondents who consumed caffeine and soft drinks were 24 times more likely to suffer from osteoporosis. It is expected for women to avoid risk factors that can cause a decrease in bone mineral density and perform early detection of osteoporosis before the age of 30 years.